Phrases in Chinese Short Stories 献你一束花 Xiàn Nǐ Yī Shù Huā 'Presenting a Bunch of Flowers to You By Feng Jicai - Hizkia Hasdin Saputra (Fakultas Sastra Universitas Darma Persada, 2022)
This paper discusses a phrase in a Chinese short story entitled 'Presenting a Bunch of Flowers to You' by Feng Jicai. Through the literature and distributional methods, many types of phrases are found in each of its sentences. The most used phrases are endocentric or nominal subordinate phrases and prepositional phrases; While the rarest ones that appear are numeralia phrases and coordinate phrases. However, the phrase numeralia classifier often appears to be an endocentric phrase-shaper. In addition, there are also contained phrases, that is, phrases in phrases, or phrases formed from other phrases. Each phrase in a sentence has its syntactical function. The most syntactic functions of phrases are as objects.